Differences in the Incidence of Major Risk Factors in Patients with Ischemic or Hemorrhagic Stroke in the Siberian Population - S. Yu. Nikulina; A. A. Chernova; D. A. Nikulin; V. A. Shulman; S. V. Prokopenko; I. M. Platunova; O. V. Marilovceva; I. I. Lebedeva; A. A. Semenchukov; D. A. Yakovleva; V. N. Maksimov; A. V. Kuskaeva (Столичная издательская компания, 2018)
Background. The study of the incidence of risk factors (RF) of stroke for primary and secondary prevention of this disease remains relevant. There are modifiable and non-modifiable RF.Aim. To study the frequency of the main RF in patients with ischemic and hemorrhagic stroke in the urban population of Krasnoyarsk (Eastern Siberia).Material and methods. Examination of 124 patients with an ischemic stroke and 28 with hemorrhagic was performed. Patients received treatment in neurologic center of Krasnoyarsk in 2014 year. The main criterion of inclusion was the confirmed diagnosis of an ischemic or hemorrhagic stroke. All patient had the clinic-tool and neurovisualizing examination and collecting the individual and family anamnesis with examination of modifiable and non-modifiable RF. The research of the neurologic status at patients both with ischemic, and with a hemorrhagic stroke was conducted by the standard technique. Based on results of computer or magnetic resonance imaging of a brain the diagnosis of an ischemic or hemorrhagic stroke was established.Results. A distinctive feature of patients with hemorrhagic stroke was the occurrence of a vascular accident in younger age (6 years earlier) in comparison with ischemic stroke. Among patients with ischemic stroke elevated body mass index (BMI) was in 87 (70.2%) patients, burdened heredity was in 8.1% of cases, and 43.5% of patients were smokers. Among patients with hemorrhagic stroke 16 (57.1%) patients had elevated BMI. People with burdened heredity were not identified among them. Smoking was found in 22 (78.6%) patients in this group.Conclusion. Improvement of treatment and prevention of an ischemic stroke are in many respects connected with clarification of RF and pathogenic mechanisms of its development. The rational pharmacotherapy directed to pointed impact on individual RF can reduce the risk of development of stroke not only at individual, but also at the population level.